Effects of high-intensity interval and moderate-intensity continuous training on the anaerobic threshold of highly trained athletes in endurance sports: a systematic review with meta-analysis - Pereira, P. E.; Esteves, G.; Carvas, N.; Azevedo, P. H. (The Journal of Sports Medicine and Physical Fitness, 2024)
INTRODUCTION: The anaerobic threshold (AT) is an important physiological index used as a parameter for predicting performance and evaluating adaptations induced by training. The aim of this study was to carry out a systematic literature review to survey the randomized studies that compared the effects of high-intensity interval training (HIIT) with the effects of moderate intensity continuous training (MICT) on the anaerobic threshold of highly trained athletes in endurance sports. EVIDENCE ACQUISITION: The following databases were searched: MEDLINE, Embase, Cochrane Wiley, PubMed, SPORTDiscus, Web of Science, and ProQuest for randomized trials. The search terms covered the areas of HIIT and MICT. This study was registered in the International Prospective Register of Systematic under the number CRD42020155474. EVIDENCE SYNTHESIS: Three studies were included for the qualitative and quantitative synthesis, totaling 72 participants, of whom 28 belonged to the MICT group and 44 to the HIIT group. CONCLUSIONS: The summary result showed that HIIT promotes greater adaptation in the AT of highly trained athletes compared to continuous training (ES=0.73; 95% CI: 0.25-1.21); however, the certainty of evidence evaluated by the GRADE method is low and heterogeneity is high (I2=82%; P<0.01).